The Heterarchy of the Roman Galli: Womanhood as Tool for Creating Religious Authority - Lätzer-Lasar, Asuman (Religion & gender, 2024)
Aim of this paper is to describe the strategies that a specific type of Roman priests, namely the galli who worshipped the goddess Mater Magna, used to enhance their own religious authority. By doing so, they were transcending a state-given political hierarchy and a long established social normativity, namely the masculine hegemony of the ancient Roman society. More generally, temporary priestly offices were highly political: every Roman statesman had to fulfil at least one such office for some time during his life. However, there were also priests and priestesses that held their offices for life. Lacking the possibility of generating prestige through warfare or political success, like Roman statesmen, the galli had to garner prestige in their lifelong priesthood, and consequently social power, through different aspects. Specific religious services, such as sacrifices, spells, etc., were one possibility. However, the galli’s power could also have been generated through social aspects, such as habitus, which is rooted in the living conditions, the cultural milieu, and the biography of an individual (Schreg, Zerres, et al. 2013, 101). This article discusses the case of the priesthood of the Mater Magna cult, a religion that emerged in Rome at the end of the 3rd century BCE and in which the priests applied a specific form of stigma management to foster their religious authority. I argue that the priesthood of the Mater Magna—although they were even defamed by the Roman intellectuals for their inconclusive sex—made use of their ‘otherness’ to generate a certain religious authority, as a form of stigma management, that elevated them in the social hierarchy and created heterarchical relations.